Performing Grief Inconsolable: Land, Lament and Love in Marina Carr’s Portia Coughlan - Vicky ANGELAKI (E-REA)
The article concentrates on Marina Carr’s seminal play Portia Coughlan (1996), examined through an ecocritical and ecofeminist lens. As the essay argues, the play’s recent revival at London’s Almeida Theatre (2023), directed by Carrie Cracknell, designed by Alex Eales and featuring Alison Oliver in the lead role, made a considerable contribution towards highlighting the roots of discomfort as well as the embodied experience of Carr’s eponymous heroine, towards emphasising concerns of grief and inconsolability, but also towards asking how consolation and agency may be conceivable for spectators within an environmentally focused staging and reading of the play. As the article proposes through an interdisciplinary reading engaging with dialogues focused on environmental discourses, the pastoral, and theatre studies (especially related to Carr), the resonance of Portia Coughlan not only endures as it approaches its thirty-year anniversary, but is also recharged vis-à-vis ecologically orientated imperatives in current theatre scholarship and the broader socio-political realm.